IMPLEMENTASI HAK-HAK TERSANGKA SEBAGAI PERWUJUDAN ASAS PRADUGA TAK BERSALAH DALAM PEMERIKSAAN DI TINGKAT PENYIDIKAN - Rebecca Marcella; Johannes Evan Budiman; Gunardi Lie; Moody Rizqy Syailendra P (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Indonesia is a state of law with the right to holding democracy in full, a democratic state is a country that prioritizes human rights in any aspect. The era that will always develop has changed the behavior of individuals and society, including criminal behavior. However, in law enforcement, a criminal must still get the human rights that have been attached to him, the principle relating to human rights in terms of law enforcement is the